2018
DOI: 10.1021/acsami.7b17054
|View full text |Cite
|
Sign up to set email alerts
|

Gelatin-Based Photocurable Hydrogels for Corneal Wound Repair

Abstract: In this study, an injectable, photocurable gelatin system, consisting of acrylated gelatin and thiolated gelatin, with tunable mechanical, biodegradation, and biological properties was used as a potential cell-supportive scaffold for the repair of focal corneal wounds. The mechanical property of hydrogels can be readily modified (postcure shear modulus of between 0.3 and 22 kPa) by varying the ratio of acrylate to thiol groups, photointensity, and solid content, and the biodegradation times also varied with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
127
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(129 citation statements)
references
References 59 publications
2
127
0
Order By: Relevance
“…Hughes et al [9] reported the photocurable thiol-acrylate hydrogels,w hich are fully cured within 0.5-1 min after UV light exposure.Doyle et al [10] studied afunctionalized hydrophilic polymer with aUV-polymerizable group,poly(ethylene glycol) diacrylate,w hich achieves fast polymerization within seconds under UV irradiation. Previous studies also demonstrate the fast nature of UV polymerization in the preparations of accommodating intraocular lens [11] and polymer electrolyte membranes.…”
mentioning
confidence: 74%
“…Hughes et al [9] reported the photocurable thiol-acrylate hydrogels,w hich are fully cured within 0.5-1 min after UV light exposure.Doyle et al [10] studied afunctionalized hydrophilic polymer with aUV-polymerizable group,poly(ethylene glycol) diacrylate,w hich achieves fast polymerization within seconds under UV irradiation. Previous studies also demonstrate the fast nature of UV polymerization in the preparations of accommodating intraocular lens [11] and polymer electrolyte membranes.…”
mentioning
confidence: 74%
“…Hughes et al . reported the photocurable thiol–acrylate hydrogels, which are fully cured within 0.5–1 min after UV light exposure.…”
Section: Methodsmentioning
confidence: 99%
“…The equilibrium water content (EWC) of the formed hydrogels was dened as the weight ratio of water content to the swollen hydrogels. 30 All the hydrogels were soaked in PBS (pH 7.4) at 37 C. Then, the hydrogels were removed from the buffer solution at different time points, placed between two pieces of dried lter paper to remove the excess solution, and then weighed (W s ). The swollen hydrogels were weighted, and the swelling ratio (%) was calculated by the following equation:…”
Section: Swelling and Degradation Behavior Of Ht Hydrogel In Vitromentioning
confidence: 99%